A novel mechanism by which c-MYC is aberrantly activated by epigenetic silencing of its antisense lncRNA in colon cancer - Hu, Xuming; Wei, Ye; Zhang, Meiying; Dou, Chunfeng; Wang, Liping; Zaib, Gul; Wu, Huixian; Guo, Wang; Wang, Xiaoyuan; Chen, Shihao; Xu, Qi; Guo, Mingzhou; et al. (Frontiers in Genetics, 2025)
BackgroundProto-oncogenes are abnormally activated in nearly all types of tumors. However, the epigenetic mechanism of proto-oncogene activation has not yet been well elucidated.MethodsThe present study involved the construction of a double-stranded cDNA library derived from gastrointestinal cancer cells, followed by high-throughput genome sequencing to select the c-MYC gene associated with colorectal cancer. Through RACE analysis, we identified the antisense RNA MYC-AS1 and its complete sequence. By investigating the cellular functions, expression of MYC-AS1, elucidating its interaction mechanism with the c-MYC gene, and exploring the impact of DNA methylation on MYC-AS1 expression, we uncover the fundamental principles and regulatory mechanisms underlying colorectal cancer development.ResultsHere, we show that a subset of proto-oncogenes,including c-MYC, possess antisense RNAs. Upregulation of c-MYC in cancer tissues was attributed to the silencing of its antisense RNA MYC-AS1 via DNA hypermethylation. MYC-AS1 RNA markedly inhibited the proliferation of cancer cells in vitro and impeded tumor growth in nude mice in vivo by repressing the expression of c-MYC via an RNAi mechanism. MYC-AS1 RNA bound directly to the HuR protein in the cytoplasm, enhancing the RNA stability of MYC-AS1. Furthermore, MYC-AS1 inhibited c-MYC-targeted gene LDHA expression. Unlike the well-characterized oncogenic long noncoding RNA PVT1, which is coamplified with MYC and enhances its stability, MYC-AS1 is epigenetically silenced and functions as a tumor suppressor through an RNAi mechanism, revealing a distinct layer of MYC regulation.ConclusionOur work provides a novel mechanism by which c-MYC is activated in cancer cells by epigenetic silencing of its antisense RNA, which functions as a tumor suppressor.